2017
DOI: 10.1177/1098612x17736656
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study to evaluate the potential use of the renal resistive index as a preliminary diagnostic tool for chronic kidney disease in cats

Abstract: Objectives Chronic kidney disease (CKD) is the most common renal pathology diagnosed in geriatric cats, and its prevalence increases with age. The arterial resistive index (RI) is important when evaluating vascular resistance and compliance, and can be applied in the kidney (renal RI [RRI]), allowing the evaluation of its vascular haemodynamics. The present study aimed to: (1) investigate in cats with CKD the relationships between the RRI and the following parameters: age, sex, body weight, plasmatic creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 30 publications
(80 reference statements)
3
35
0
Order By: Relevance
“…AKI can slowly develop into chronic renal failure and eventually become an independent risk factor for death. There are many factors that can trigger AKI such as hypovolemia, shock, major surgery, trauma, and heart failure [ 16 ], of which the most common factor is sepsis. According to some research, the mortality rate of patients with septic AKI is much higher than that of patients with AKI of other causes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…AKI can slowly develop into chronic renal failure and eventually become an independent risk factor for death. There are many factors that can trigger AKI such as hypovolemia, shock, major surgery, trauma, and heart failure [ 16 ], of which the most common factor is sepsis. According to some research, the mortality rate of patients with septic AKI is much higher than that of patients with AKI of other causes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…SWE was performed in this study because it is the newest USE technique [44]; it also provides better information on elasticity than SE, in which the result is highly dependent upon operator experience [45]. Other imaging techniques have also been used to facilitate an early CKD diagnosis in cats, such as: contrast-enhanced ultrasound examination in domestic and purebred cats [46], and renal resistive index (RRI) in domestic cats [47]. However, methods such as RRI are difficult to evaluate, especially in CKD cats with renal vascular impairment and decreased renal blood flow [47].…”
Section: Discussionmentioning
confidence: 99%
“…Other imaging techniques have also been used to facilitate an early CKD diagnosis in cats, such as: contrast-enhanced ultrasound examination in domestic and purebred cats [46], and renal resistive index (RRI) in domestic cats [47]. However, methods such as RRI are difficult to evaluate, especially in CKD cats with renal vascular impairment and decreased renal blood flow [47]. Peng and colleagues [25] reported that human patients with CKD had stiffer kidneys than healthy people, when using SWE.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the values of RI and PI for the kidneys of healthy cats and animals with kidney disease being previously reported, 6,8,11,21–26 their clinical utility remains unclear. This doubt is probably related to diverse upper limits proposed for felines.…”
Section: Introductionmentioning
confidence: 99%